Innovations in Russian industries: Conditions for implementation and impact on competitiveness - Igor Gurkov (Journal for East European Management Studies, 2005)
Based on the result of a survey of 1500 Russian industrial companies we not only clarified the intensity of particular innovations but also interconnections between technological and managerial innovations. We also determined the institutional factors that affect the intensity of particular innovations, i.e. presence of foreign ownership, openness of local markets to international competition and inclusion of companies into large corporations to/that foster innovations. At the same time, the rigidity of organizational structures and inertia of local production networks put serious limitation on radical product and technological innovations. The further development of Russian industries will largely depend on organizational flexibility of corporations and on increasing mutual trust within local business networks. – – Unter Nutzung der Ergebnisse einer Umfrage unter 1500 Industrieunternehmen werden nicht nur die Intensität von spezifischen Innovationen, sondern auch die Zusammenhänge zwischen Technologie- und Managementinnovationen nachgewiesen. Weiterhin wurden auch die institutionellen Faktoren bestimmt, die diese Innovationen beeinflussen wie das Vorhandensein ausländischen Eigentums, die Öffnung des Marktes zur internationalen Konkurrenz und die Einbindung von Firmen in große Unternehmen, um Innovationen voranzutreiben. Gleichzeitig erschweren rigide Organisationsstrukturen und lokale Produktionsnetzwerke radikale Produkt- und Technologieinnovationen immens. Die zukünftige Entwicklung der russischen Industrien wird weitgehend von der organisationellen Flexibilität der Unternehmen und dem wachsenden gegenseitigenVertrauen innerhalb lokaler Handelsnetzwerke abhängen.
Keywords: 650; innovations; competitiveness; organizational design; strategic architecture